Rancang Bangun Sistem Pemantau Tamu - Mar Qosim; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
People in ancient times when visiting someone's home by calling the owner of the house. But that way is not right to do, if the homeowner is not at home, so the homeowner cannot hear the voice of the guest calling. Therefore, a guest monitoring system was created, this system is placed on the front wall of the house. This system sends a short message to the Telegram Application that is on the homeowner's Smartphone. Using Esp32 as a microcontroller, four Passive Infrared Sensor (PIR) sensors are used as guest detectors. The Internet Protocol (IP) camera is directed to guests, so homeowners can find out who guests are visiting. Every visiting guest has a voltage difference, on the pir sensor 1 if there are guests, the voltage on the pir sensor is 3.38v, pir 2 if there are guests, the voltage on the pir sensor is 3.36v, pir 3 if there are guests, the voltage on the pir sensor is 3.37v, and all pir sensors are zero if there are no guests. The purpose of research is how to design a guest monitoring system. The research results make it easy for homeowners to monitor guests visiting their homes. The homeowner reads the incoming message to the Telegram application when the PIR sensor detects the infrared existence of the guests, then opens the IP camera app to find out who guests are visiting.Keywords: Esp32, Sensor Pir, Motor Servo, Telegrambot.